Relevansi Kitab Ta’lim Muta’allim dengan Pendidikan Masa Kini (Tinjauan Faktor-faktor Pendidikan) - Purbajati, Hafidz Idri (Jurnal Munaqasyah, 2019)
Abstract: Throughout the history of human education is a very important necessity is absolutely necessary, so that education is researched and developed how to find new concepts as a logical consequence of the times. The development then led to a modernization whose consequence was to begin to question the relevance of old or classical concepts. the question posed by those who are not sincere is the old method can not answer the development of science and technology. Is everything completely true? what about the classic book that is often used as a reference in the process of dedication that is ta'lim Muta'llim ?. The Book of Ta'lim Muta'alim is a yellow book in its home area, which is around the Middle East, this yellow book called Al-Kutub Al-Qadimah as a counter to Al-Kutub Al-Ashriyah. The education based on the yellow book has succeeded in forming a moral society and interacting with different levels of intelligence ranging from the talib (pupil) and mutha'alim to the alim or mu'alim (kyai). Munurut A. Chozin Nasuha, if examined yellow book will all refer to the translation of Al-Qur'an and Al-hadith or most take the legitimacy of these two sources of teaching. "So the yellow book is a treasure that can not be ignored".